(untitled) (SCIÉNDO INGENIUM, 2022)
The present investigation is focused on determining the legal situation of the cryopreserved human embryo in Peruvian civil law from the ruling of the Inter-American Court of Human Rights in the "Case of Artavia Murillo et al. (In vitro fertilization) Vs. Costa Rica", beginning the study of file No. 02005-2009-PA/TC (case of the “Morning After Pill”) and Exp. 30541-2014-0-1801-JR-CI-01 (Amparo that authorizes the free distribution of levonorgestrel), within the framework of legislation and jurisprudence foreign, having as hermeneutical guideline the principle pro homine and pro debilis. It is concluded that the national legal system recognizes the legal status of the cryopreserved human embryo as a person, which contradicts the standard established by the Inter-American Court which excludes it from the scope of Article 4.1 of the Convention.